Peripheral nervous system involvement in SARS-CoV-2 infection: a review of the current pediatric literature - Perilli, Lorenzo; Fetta, Marina; Capponi, Martina; Guido, Cristiana Alessia; Grosso, Salvatore; Iannetti, Paola; Spalice, Alberto (Frontiers in Neurology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was identified as the pathogen responsible for the pandemic health emergency declared by the World Health Organization in March 2020. During the first part of the pandemic, adults showed mild to severe respiratory symptoms. Children seemed initially exempt, both from acute and subsequent complications. Hyposmia or anosmia were promptly identified as the main symptoms of acute infection, so neurotropism of SARS-CoV-2 was immediately suspected. As the emergency progressed, post infectious neurological complications were described also in paediatric population. Cranial neuropathy has been reported in pediatric patients in connection with acute SARS-CoV-2 infection, as an isolate post infectious complication or in the context of the multisystem inflammatory syndrome in children (MIS-C). Neuroinflammation seems to be caused by immune and autoimmune reactions, and not directly by the viral invasion, but so far, no specific autoantibody has been identified. Some authors highlighted that the enhancement of the cranial roots and ganglia in neuroimaging isn’t always observed in children presenting with cranial neuropathies. Even if a variety of case reports were published, opinions about an increased incidence of such neurologic diseases, linked to SARS-CoV-2 infection, are still controversial. Facial nerve palsy, ocular movements abnormalities and vestibular alterations are among the most reported issues in paediatric population. Moreover, an increased screen exposure imposed by social distancing led to acute oculomotion’s disturbance in children, not primarily caused by neuritis. The aim of this review is to suggest food for thought on the role of SARS-CoV2 in neurological conditions, affecting the peripheral nervous system to optimise the management and care of paediatric patients.